Utilising flipped classrooms to enhance the reading of short stories in English as a Second Language (ESL) context: a literature review - Shafie, Bukhari; Fazeli Kader, Fazelinah; Abdul Rahman, Amirah Raihana (Centre for Languages and Pre-University Academic Development, IIUM, 2024)
Based on past studies, it has been found that students' motivation, engagement, and creativity in the classroom are positively impacted by the use of technology-driven blended learning, such as flipped classrooms. According to the flipped classroom model, students study the instructional materials outside of class and use the classroom for discussion, explanation, and application of what they have learned under the guidance of a facilitator. This paper found that the flipped classroom approach is effective in enhancing ESL skills: reading, listening, speaking, and writing. Also, it has been studied that the use of literary components in ESL can amplify students’ linguistic knowledge, cultural awareness, and critical thinking. Considering this, this paper aims to further investigate and assess existing literature on the effectiveness of flipped classrooms on the reading of short stories in ESL classrooms. Based on the findings, it is noted that the studies conducted on the reading of literary components such as short stories are still scarce and under-researched through the flipped classroom approach. Thus, this paper recommends that researchers should delve into investigating the efficacy of the flipped classroom approach to enhance the reading of short stories in ESL. Additionally, the benefits and best practices of using flipped classrooms in ESL are also extensively discussed in this literature review.